Brain and Gut CRF Signaling: Biological Actions and Role in the Gastrointestinal Tract - Tache, Yvette; Larauche, Muriel; Yuan, Pu-Qing; Million, Mulugeta (Current Molecular Pharmacology, 2018)
Background: Corticotropin-releasing factor (CRF) pathways coordinate behavioral, endocrine, autonomic and visceral responses to stress. Convergent anatomical, molecular, pharmacological and functional experimental evidence supports a key role of brain CRF receptor (CRF-R) signaling in stress-related alterations of gastrointestinal functions. These include the inhibition of gastric acid secretion and gastric-small intestinal transit, stimulation of colonic enteric nervous system and secretorymotor function, increase intestinal permeability, and visceral hypersensitivity. Brain sites of CRF actions to alter gut motility encompass the paraventricular nucleus of the hypothalamus, locus coeruleus complex and the dorsal motor nucleus while those modulating visceral pain are localized in the hippocampus and central amygdala. Brain CRF actions are mediated through the autonomic nervous system (decreased gastric vagal and increased sacral parasympathetic and sympathetic activities). The activation of brain CRF-R2 subtype inhibits gastric motor function while CRF-R1 stimulates colonic secretomotor function and induces visceral hypersensitivity. CRF signaling is also located within the gut where CRF-R1 activates colonic myenteric neurons, mucosal cells secreting serotonin, mucus, prostaglandin E2, induces mast cell degranulation, enhances mucosal permeability and propulsive motor functions and induces visceral hyperalgesia in animals and humans. CRF-R1 antagonists prevent CRF- and stressrelated gut alterations in rodents while not influencing basal state. Discussion: These preclinical studies contrast with the limited clinical positive outcome of CRF-R1 antagonists to alleviate stress-sensitive functional bowel diseases such as irritable bowel syndrome. Conclusion: The translational potential of CRF-R1 antagonists in gut diseases will require additional studies directed to novel anti-CRF therapies and the neurobiology of brain-gut interactions under chronic stress.
Keywords: CRF receptor antagonists